DEACIDIFICATION OF ADLAY SEED (COIX LACHRYMA-JOBI VAR. MAYUEN) MISCELLA WITH ANION-EXCHANGE RESIN - DU, SHAO-LONG; ZHOU, CHUN-SHAN; YANG, LIU-QING (Journal of food process engineering, 2007)
This study examined the potential of ion-exchange adsorption technique for the deacidification of adlay seed miscella. The adsorption properties, including the adsorption isotherms, thermodynamics and kinetics, of free fatty acids (FFAs) onto anion-exchange resin LSD-263 were investigated. Regression results showed that the Freundlich model can describe the adsorption isotherm better than the Langmuir model can. The positive values of enthalpy indicated that an endothermic process in our study range - the negative value of free energy indicated the spontaneous nature of the adsorption process - and the positive values of entropy showed the increased randomness at the solid/liquid interface during the adsorption process. The Lagergren first-order model and the Ho pseudo second-order model were used to investigate the adsorption data and Ho's model could present the experimental data better than Lagergren's model could. The adsorption constant increase with temperature indicated that higher temperature would benefit the adsorption process. Analysis of adlay seed oils revealed that the application of LSD-263 could get a high % removal of FFAs (about 90%) and partly remove phospholipids (68.58%) and pigments (64.41%) without significant change of oil content and fatty acid composition. Conventional neutralization of vegetable oils by alkali or physical refining is considered very energy consuming. In addition, all the refining operations subject oils to high temperatures. High temperatures seem to be the most harmful parameter, which is responsible for hydrolytic, oxidative and polymerization alterations. Improving the quality of processed oils by reducing side effects and energy consumption has been among the most attractive research areas throughout the past half-century. Due to its characteristic as a highly effective and energy-saving technology, ion-exchange processing has the potential of being an alternative vegetable-refining technique. However, there has not been much fundamental research concerning the adsorption of free fatty acids from vegetable oils by anion-exchange resins. Deacidification of vegetable oil with ion-exchange resins can be operated at low temperature (<50C). These mild conditions, which contrast with the condition in industry practices, are expected to preserve the sensitive and bioactive components in vegetable oils. Moreover, due to high separation effectiveness, ion-exchange processing can be done with vegetable miscella itself without any further solvent removal by evaporation.